Effect of self-efficacy and empathy characteristics of post-graduate residents on local anesthesia administration performances: Pilot study - ÖZÇELİK, SELÇUK MERT; AKYÜZ, SERAP HATİCE (WILEY, 2022)
Purpose The Profile and Competences for the European Dentist document addresses some competencies as a must for graduating dentists, some of which are stated as providing humane and compassionate care to all patients and administering local anesthesia for pain management. Within this perspective, this study aims to investigate the effect of self-efficacy and empathy characteristics of post-graduate residents (post-grads) on the perceived pain and anxiety scores of children during local anesthesia administrations. Materials and methods Ten pediatric dentistry post-grads and 91 children aged between 5 and13 years participated in the study. Post-grads performed 120 injections as part of their routine dental treatment in children. Demographic data, self-efficacy, and empathy scale scores of post-grads, anxiety, and pain scores of children were recorded during injections. Results Self-efficacy scale scores of residents ranged between 66 and 74 with a mean score of 69.80 +/- 2.69. Empathy scale scores were between 77 and 97 and the mean was 89.20 +/- 6.24. Significant and negative correlations were observed between self-efficacy scores of post-grads and pain scores of children (r = -0.205 and p = 0.025). Empathy scores of post-grads established a significant and positive correlation with children's anxiety scores (r = 0.244 and p < 0.007). Conclusions Self-efficacy and empathy characteristics of post-grads were found to have an impact on the perceived pain and anxiety scores of children during local anesthesia administrations. Empathetic post-grads with higher self-efficacy provided an enhanced local anesthesia experience for child patients. Therefore, educational programs should also be organized aiming to develop self-efficacy and empathy characteristics of post-grads for a more humane and compassionate dental experience in child patients.
Keywords: child; dental anxiety; local anesthesia; pain; self-efficacy; ANXIETY; FEAR; BEHAVIORS; CHILDREN; DEVICE; PAIN